2020
DOI: 10.1021/acs.nanolett.9b04764
|View full text |Cite
|
Sign up to set email alerts
|

Groove-Assisted Global Spontaneous Alignment of Carbon Nanotubes in Vacuum Filtration

Abstract: Ever since the discovery of carbon nanotubes (CNTs), it has long been a challenging goal to create macroscopically ordered assemblies, or crystals, of CNTs that preserve the one-dimensional quantum properties of individual CNTs on a macroscopic scale.Recently, a simple and well-controlled method was reported for producing wafer-scale crystalline films of highly aligned and densely packed CNTs through spontaneous global alignment that occurs during vacuum filtration [Nat. Nanotechnol. 11, 633 (2016)].However, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 14 publications
1
53
0
Order By: Relevance
“…The analysis showed that the neat SWCNT film was composed of intertwined bundles of SWCNTs arranged in an isotropic fashion as expected for material prepared by unconstrained vacuum filtration. Spontaneous alignment of SWCNTs occurs only when special conditions are established, e.g., filtration rate is limited to a few mL/h of the dispersion [32,33], which was not the case herein. Regarding purity, no obvious signs of contamination were discerned in the material.…”
Section: Resultsmentioning
confidence: 84%
“…The analysis showed that the neat SWCNT film was composed of intertwined bundles of SWCNTs arranged in an isotropic fashion as expected for material prepared by unconstrained vacuum filtration. Spontaneous alignment of SWCNTs occurs only when special conditions are established, e.g., filtration rate is limited to a few mL/h of the dispersion [32,33], which was not the case herein. Regarding purity, no obvious signs of contamination were discerned in the material.…”
Section: Resultsmentioning
confidence: 84%
“…Vacuum filtration is a method of covering the required material on the membrane by the negative pressure caused by air extraction. [99] For example, Yang et al prepared asymmetric Janus membrane from FOOH Kevlar solution and ZnO Kevlar solution by vacuum filtration using double layer composite, as shown in Figure 10b. [59] Vacuum filtration could not only simply fabricate Janus membrane, its operation is simple, therefore it has the potential of large-scale preparation of Janus membrane.…”
Section: Double-layer Modificationmentioning
confidence: 99%
“…Vacuum filtration is a method of covering the required material on the membrane by the negative pressure caused by air extraction. [ 99 ] For example, Yang et al. prepared asymmetric Janus membrane from FOOH Kevlar solution and ZnO Kevlar solution by vacuum filtration using double layer composite, as shown in Figure 10b.…”
Section: Design and Fabricationmentioning
confidence: 99%
“…Furthermore, the isotropic distribution of these building blocks within the network contributes its share to the extrinsic component of resistance, which must be considered. Recent advances in the field alleviate these problems by substantially improving the internal structure alignment [ 21 , 22 , 23 , 24 ]. Nevertheless, the intrinsic factors of resistance remain a problem.…”
Section: Introductionmentioning
confidence: 99%